Effects of elicitors on the growth and active compounds of Panax vietnamensis cells in the bioreactor - Van Men Chu; Tuan Anh Vu (Vietnam Journal of Science, Technology and Engineering, 2017)
In this study, the effects of elicitors on the growth and bioactive ingredients of Panax vietnamensis cell mass are evaluated. The medium composition was fixed with a MS liquid medium supplemented with 6.42 mg/ml NAA, kinetin of 0.11 mg/l, saccharose of 34.3 g/l, a pH of 5.6-5.8, temperature of 24-26oC, conducted at 50 rpm, and culture time of 14 days. The results showed that the best elicitor is jasmonic acid, at a concentration of 100 µmol/l, and for an optimal exposure of the bioactive ingredients to jasmonic acid for 12 days and 14 days after starting the culture. Under select conditions, the cell mass yield was 20.01 g/l and contents of ginsenoside Rg1, Rb1, and Rd were 0.288, 0.302, and 0.146%, respectively.